FIXED ASSETS - M. Aulia Rahman; Yusri Hamzi, Muksal Mina, Muhammad Akbarri (Adisam Publisher, 2024)
Fixed assets are tangible assets that have had economic benefits for more than one year and are used by the company for operational purposes, not for resale. This type of asset includes equipment, furniture, tools, machinery, buildings, and land Assets remain classified as long-term or relatively permanent assets due to their visible physical nature and long service life. Research methodology Researchers apply a type/methodology of research known as Library Research in this research. Researching and asking questions in a library can be used more than just obtaining research data. That means the study of the library can only use the materials of the collection of libraries and do not have to go down to the field. But experts say that the study of the library is a way of obtaining information by reading books, articles, notes, and reports related to the problems that are being faced.